Politics and feminism: An introduction - Arneil, Barbara (Blackwell, 1999)
This book addresses the question of gender and feminism in western political theory and practise. It provides students with both the theoretical and historical underpinnings of women's exclusion from politics, and the feminist response to this exclusion.
Keywords: amériques; approches et analyses; cours; discipline; discriminations; europe; fem1000; histoire et politique; inégalités; occident; premier cycle; régions géographiques; science politique; science politique et droit; systèmes d'oppressions; thématiques; théories féministes; théories politiques

With other eyes: looking at race and gender in visual culture - Bloom, Lisa (University of Minnesota Press, 1999)
Feminist and multiculturalist efforts to uncover the assumptions underpinning the production of art have transformed our understanding of visual culture. The field of art history, however, continues to downplay the race and gender politics informing its own interpretative practices. With Other Eyes brings together leading cultural theorists to demonstrate how feminist, postcolonial, and antiracist concerns can successfully and imaginatively be incorporated into the study of art. Rejecting strict definitions of “high art,” the contributors add photography, installation art, and film to the list of more conventional art forms to examine, for example, the construction of black femininity as influenced by Josephine Baker, Grace Jones, and the women depicted in Picasso’s Les Desmoiselles d’Avignon;the nationalist and class premises in nineteenth-century British Museum guidebooks; and the gendered visions of colonial discourse in advertisements for Ralph Lauren and the Body Shop.
Section: VIII-268 p. : illustrations ; 26 cm
Keywords: approches et analyses; arts; cours; discipline; féminisme décolonial; féminisme pop; har4610; histoire de l'art; histoire et politique; premier cycle; racisme; représentation des femme*; systèmes d'oppressions; thématiques

Mémoires d'une bataille inachevée : la lutte pour l'avortement au Québec, 1970-1992 - Desmarais, Louise (Éditions Trait d'union, 1999)
Chronique des événements entourant la lutte pour l'avortement libre et gratuit, l'une des plus importantes revendications du mouvement féministe québécois. Les différents groupes qui ont mené le combat, leurs discours et la place de leurs actions dans la dynamique des relations qu'ils entretenaient avec les gouvernements et le mouvement anti-avortement. Etude appuyée sur une solide documentation.
Section: 441 pages ; 23 cm
Keywords: 1800-1899; 1900-1999; amérique du nord; amériques; approches et analyses; avortement; canada; droits des femmes*; histoire des femmes*; histoire et politique; justice reproductive; militance; patriarcat; périodes historiques; québec; régions géographiques; systèmes d'oppressions; thématiques

Queer theory: Under construction - Dilley, Patrick (International Journal of Qualitative Studies in Education, 1999)
This article outlines how the concepts of queer and queer theory have been applied to qualitative studies. The multiple definitions of queer are examined, to foster an understanding of the positions from which theorists have utilized the concept to examine a number of disciplines. The advancement of the tenets of queer theory is outlined chronologically, to display the evolution of the theory through intradisciplinary applications. The body of qualitative works utilizing queer theory is categorized (language, literature, and arts; history; life histories / life stories; and queer theory as praxis) and juxtaposed. In addition, efforts to define and enact a "queer pedagogy" are analyzed. Suggestions for further application of queer theory in education, ethnography, and qualitative studies conclude the article.
Keywords: approches et analyses; discipline; discours dominant; ethnographie; histoire et politique; hétérosexisme; pédagogie; pédagogie queer; queer; ressource en ligne; sciences de l'éducation; systèmes d'oppressions; thématiques; éducation; étude qualitative

Une organisation maternaliste au Québec la Fédération nationale Saint-Jean-Baptiste et la bataille pour le vote des femmes - Hébert, Karine (Revue d'histoire de l'Amérique française, 1999)
Cet article présente, à la lumière des développements récents de l'historiographie féministe, une nouvelle interprétation de la Fédération nationale Saint-Jean-Baptiste. Cette réinterprétation se base sur un concept assez nouveau: le maternalisme, défini comme une catégorie d'analyse utilisée pour qualifier les mouvements de femmes chez qui la maternité constituait le point central de l'idéologie et de l'argumentation. Nous examinons, entre autres, le modèle féminin véhiculé par la FNSJB pour constater qu'il correspondait au modèle traditionnel de « la femme », celui qui effectuait une équation entre la femme et la mère. La maternité n'était toutefois pas perçue par la FNSJB comme une fonction limitative, mais bien comme une ouverture vers la société. Elle a donc dû redéfinir les frontières entre les sphères privée et publique pour permettre aux femmes de transgresser celles du foyer et faire bénéficier la société de leur influence maternelle. Le cadre d'analyse élaboré dans la première partie est ensuite appliqué à un cas concret de revendication: la bataille pour le vote des femmes.
https://www.erudit.org/en/journals/haf/1999-v52-n3-haf219/005467ar/
Keywords: 1900-1909; 1900-1999; 1910-1919; amériques; approches et analyses; canada; changement social; corps; cours; droit de vote; fem1000; histoire des femmes*; histoire et politique; maternité; militance; mouvements féministes; patriarcat; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques

De la clandestinité à l'affirmation : pour une histoire de la communauté gaie montréalaise - Higgins, Ross (Comeau & Nadeau, 1999)
Survol historique de la communauté gaie-lesbienne de Montréal. D'après l'auteur, ce premier volume sera suivi d'une publication ultérieure où son enquête sera présentée de façon plus globale.
Section: 165, [2] p
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; discours dominant; his4860; histoire; histoire et politique; hétérosexisme; identités LGBTQIA2+; justice sociale; militance; montréal; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; shm4000; soc2014; systèmes d'oppressions; thématiques

Differencing the canon: feminist desire and the writing of art's histories - Pollock, Griselda (Routledge, 1999)
In this major book, Griselda Pollock engages boldly in the culture wars over `what is the canon?` and `what difference can feminism make?` Do we simply reject the all-male line-up and satisfy our need for ideal egos with an all women litany of artistic heroines? Or is the question a chance to resist the phallocentric binary and allow the ambiguities and complexities of desire - subjectivity and sexuality - to shape the readings of art that constantly displace the present gender demarcations?
Keywords: approches et analyses; artistes féministes; arts; canon; cours; discipline; discours dominant; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; premier cycle; ressource en ligne; sexisme; systèmes d'oppressions; thématiques